Shortcomings in Design and Analysis of Clinical Studies on Bleeding and Thrombosis in Patients with Cirrhosis - Northup, Patrick; Davis, Jessica (Seminars in Thrombosis and Hemostasis, 2020)
Significant gains have been made in our understanding of bleeding and thrombosis in patients with liver disease in recent years, with concurrent exponential growth in the scientific literature published in this realm. Clinical studies of this population are challenging for multiple reasons including some hurdles unique to this population. Cirrhosis patients as a whole, especially those with decompensated cirrhosis, are a high-risk and heterogeneous population prone to serious adverse events. Outcomes of bleeding and thrombosis are relatively rare and lack standardized, validated definitions. Standard practices for clinical care have evolved rapidly and rendered some control data uninformative. We aim to highlight these challenges and make recommendations for best practices for future study design and implementation. Multidisciplinary collaboration with proceduralists, careful study design including attention to validated clinically relevant outcomes, and aggressive pursuit of all funding streams will be key to continued scientific success in this burgeoning field.
Keywords: portal vein thrombosis; esophageal varices; procedural bleeding; anticoagulants; clinical study design